Eddies: Fluid Dynamical Niches or Transporters?–A Case Study in the Western Baltic Sea - Vortmeyer-Kley, Rahel; Lünsmann, Benedict; Berthold, Maximilian; Gräwe, Ulf; Feudel, Ulrike (Frontiers in Marine Science, 2019)
Fluid flows in the ocean have a strong impact on the growth and distribution of planktonic communities. In this case study we apply a Lagrangian eddy detection and tracking tool and a transfer operator approach to data from a coupled hydrodynamical-chemical-biological model of the Western Baltic Sea and study the effects of eddies on plankton in the blooming period March to October 2010. We investigated the residence times of water bodies inside these eddies using a tracer analysis and found that eddies can act in two different ways: They can be transporters of an enclosed water body embodying nutrients and the plankton community and export them from the coast to the open sea and they can act as fluid dynamical niches enhancing the growth of certain species or functional groups by providing optimal temperature and nutrient composition.